The Effect of Gender Chief Executive Officer (CEO), Gender Audit Committee, KAP Size, Profitability and Solvency on Audit Delay - Nanan Sunandar; Erma Susilawati Hidayat (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The purpose of this research is to analyze the effect of CEO Gender, Audit Committee Gender, Public Accounting Firm Size, Profitability and Solvency on Audit Delay. The data used is from the Indonesia Stock Exchange during 2016 – 2020. This sampling technique uses a purposive sampling technique. The results of this study indicate that the Chief Executive Officer (CEO) Gender, Audit Committee Gender and Profitability have an effect on Audit Delay, while KAP Size and Solvency have no effect on Audit Delay. And simultaneously Gender Chief Executive Officer (CEO), Gender Audit Committee, KAP Size, Profitability and Solvency affect the Audit Delay of manufacturing companies for the 2016-2020 period.